2017
DOI: 10.1016/j.molbiopara.2016.12.008
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear RNA binding protein RBP33 influences mRNA and spliced leader RNA abundance in Trypanosoma brucei

Abstract: RNA recognition motif (RRM) containing proteins are important regulators of gene expression in trypanosomes. Here we expand our current knowledge on the exclusively nuclear localized RRM domain containing protein RBP33 of Trypanosoma brucei. Overexpression of RBP33 leads to a quick growth arrest in G2/M in bloodstream form cells likely due to an overall mRNA- and spliced leader abundance decrease while the ribosomal RNAs remain unaffected. The recombinant RBP33 binds to poly(A) and random sequence RNA in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…3). Overexpression of RBP33 also resulted in a decrease of total mRNA [29], an observation we noted previously in metacyclics when compared to procyclics [7]. Thus, RBP33 could play a role in the establishment of metacyclics and in particular in the generation of metacyclics uncharacteristically arrested at the G2/M checkpoint.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…3). Overexpression of RBP33 also resulted in a decrease of total mRNA [29], an observation we noted previously in metacyclics when compared to procyclics [7]. Thus, RBP33 could play a role in the establishment of metacyclics and in particular in the generation of metacyclics uncharacteristically arrested at the G2/M checkpoint.…”
Section: Resultsmentioning
confidence: 58%
“…This is an intriguing result, since it was previously shown that overexpression of RBP33 leads to a rapid growth arrest in G2/M, i.e. accumulation of 2K2N cells [29], which is one of the configurations enriched in metacyclics (13%; Fig. 3).…”
Section: Resultsmentioning
confidence: 66%
“…RBP33 is an essential nuclear protein, so its association with DRBD18 but not ZC3H28 corresponds to the localisations of the two proteins. RBP33 associates with non-coding RNAs, especially from antisense transcription (Fernandez-Moya et al 2014), but its depletion led to loss of mRNA and spliced leader RNA (Cirovic et al 2017), suggesting a link to splicing. Both DRBD18 and ZC3H28 enriched various ribosomal proteins and RNA-binding proteins, including both poly(A) binding proteins (PABP1 and PABP2), ALBA2, ALBA3, DRBD2, DRBD3, ZC3H9, ZC3H34, ZC3H39, ZC3H40, UPF1, HNRNPH/F and TRRM1.…”
Section: Resultsmentioning
confidence: 99%
“…RBP33 is an essential nuclear protein, so its association with DRBD18 but not ZC3H28 corresponds to the localisations of the two proteins. RBP33 associates with non-coding RNAs, especially from antisense transcription (77), but its depletion led to loss of mRNA and spliced leader RNA (78), suggesting a link to splicing. Both DRBD18 and ZC3H28 enriched various ribosomal proteins and RNA-binding proteins, including both poly(A) binding proteins, ALBA2, ALBA3, DRBD2, DRBD3, ZC3H9, ZC3H34, ZC3H39, ZC3H40, UPF1, HNRNPH/F and TRRM1.…”
Section: Bmentioning
confidence: 99%